Religious development and child personality: What does religious psychology say about them? - Wati, Salmi; Amelia, Rezki; Hidayatina, Hidayatina; Gusmirawati, Gusmirawati (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
This research aims to reveal how religious guidance in the formation of Islamic personality in children is seen from the study of religious psychology. Basically, personality and religious development in childhood is the responsibility of parents at home and teachers at school. So that the development can run as it should and can produce the expected results, it should be in an effort to foster the personality and religion of a child adjusted to his religious nature and religious development that is being passed. The research method used in this research is library research. By using descriptive analysis methods by collecting data, compiling or classifying, analyzing, and interpreting it. The results showed that the period of children is the beginning of religious coaching and personality. If the child's personal development is carried out properly, then in adolescence will not have difficulty in building his personality. Conversely, if the child fares poorly, where personal coaching in his family is not carried out properly and in school is less helpful, then he will face a difficult adolescence and his personal coaching will be very difficult.